MARKETING MIX FACTORS THAT INFLUENCE THE DESIRE TO PURCHASE FRUIT BEVERAGES IN THE CITY OF BOGOR - Iffatul Ulfah; Ujang Sumarwan; Dodik Ridho Nurrochmat (Indonesian Journal of Business and Entrepreneurship (IJBE), 2016)
The objectives of this research were 1) to analyze marketing mix factors that influence the desire to purchase fruit beverages, 2) to formulate the marketing strategies of fruit beverages at restaurant based on fruit beverages in the city of Bogor. This research was conducted by using descriptive methods through survey approach. Data was collected in questionnaires, using non probability sample approach with convenience sampling technique. Variables measured  were 7P’s marketing mix factors, namely product, place, price, promotion, physical evidence, process and people. The analysis that were used were descriptive analysis and discriminant analysis. The result of this research shows that price and physical evidence were two factors that discriminate consumer behaviour. This means that the purchase intention (desire) between consumers who buy and consumers who do not buy fruit beverages were affected by price and physical evidence factors. The discriminant function that discriminate consumers purchase intention is D = -3,339+0,619Physical+0,899Price and cut-off value -0,18624. This means that if discriminant value (D)is higher than -0,18624, the consumer belongs to the group of consumer who will buy the fruit beverages and vice versa.Keywords: consumer behaviour, purchase intention, marketing mix, discriminant analysis